2016
DOI: 10.1016/j.renene.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of torrefied pine as a gasification fuel using a bubbling fluidized bed gasifier

Abstract: a b s t r a c tTorrefied biomass has higher C/O ratio, resulting in improved heating value and reduced hygroscopic nature of the biomass, thus enabling longer storage times. In the southeastern United States, pine is has been identified as a potential feedstock for energy production. The objective of this study was to understand the performance of torrefied pine as a gasification fuel in a bench-scale bubbling fluidized bed gasifier. The gasification of torrefied pine was carried out at 790, 935 and 1000 C and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…The highest levels for the combination CO + H 2 were obtained for OS at both S/A ratios (50/50 and 75/25), though it was slightly higher in the second case (35% and 30% at SR = 0.2 and 37%-42% at SR = 0.1). From the slight differences between PIN-CHE and their torrefied couples PINT-CHET, it can be concluded that torrefaction does not significantly improve the gasification properties for either hardwood or softwood, as previously reported by Kulkarni et al [26].…”
Section: Effect Of Sr and Steam/air Ratio On The Product Gas Propertiessupporting
confidence: 78%
See 1 more Smart Citation
“…The highest levels for the combination CO + H 2 were obtained for OS at both S/A ratios (50/50 and 75/25), though it was slightly higher in the second case (35% and 30% at SR = 0.2 and 37%-42% at SR = 0.1). From the slight differences between PIN-CHE and their torrefied couples PINT-CHET, it can be concluded that torrefaction does not significantly improve the gasification properties for either hardwood or softwood, as previously reported by Kulkarni et al [26].…”
Section: Effect Of Sr and Steam/air Ratio On The Product Gas Propertiessupporting
confidence: 78%
“…In this case OS reaches values close to 50% in the SR range between 0.2-0.3, followed by PINT and AS with yields over 40% and 35%, respectively, in the same range as in the previous case, generally considered as the optimum range for biomass gasification in other previous works [26,43,44]. All the other samples reach levels below 30%, with the worst values, just slightly over 10%, corresponding to CHE and CS.…”
Section: Effect Of Sr and Steam/air Ratio On The Product Gas Propertiessupporting
confidence: 72%
“…7c) concentrations are slightly lower for torrefied than for raw samples. Similar tendencies from air gasification experiments of raw and torrefied pine have been reported in literature [34]. Therefore, if the main objective of the gasification process is to produce hydrogen, the use of torrefied biomass as feedstock could be interesting, although further research on this topic is still necessary.…”
Section: Gasification Of Different Types Of Lignocellulosic Biomasssupporting
confidence: 77%
“…to decrease with the increase in the gasification temperature due to an enhanced steam gasification of the char [34]. Moreover, the rate of reactions involved in the steam gasification process at lower temperatures (700 ºC) seems to be extremely low compared with those at higher temperatures, such as 900 ºC, which results in lower char conversion and hence lower thermal efficiency [16].…”
Section: F)mentioning
confidence: 99%
See 1 more Smart Citation